Salih Zeki ve Asar-ı Bakiye'nin 1960'larda Yapılmış Bir Çevirisi - ŞENKON, HÜLYA (İstanbul Üniversitesi Edebiyat Fakültesi, 2005)
Together with the Kamus-i Riyaziyât (Encyclopaedia of Mathematics), the Asâr-ı Bâkiye is Salih Zeki’s major work on the history of mathematics and astronomy. The first volume covering the history of spherical trigonometry and the second treating the history of arithmetics were both published in Istanbul in 1913. The third volume on astronomy remained unpublished. A project of translating the first three volumes into modern Turkish was initiated by Nazım Terzioğlu (1912-1976) professor of mathematics at Istanbul University in early 1960s or possibly earlier. A commission composed of professors of mathematics, astronomy, physics and history of medicine was formed in 1961 to decide on the publication of Salih Zeki’s works. The manuscript of the Asâr-ı Bâkiye translation which consists of 411 type-written pages is actually kept in the archives of the Turkish Mathematical Society. The present paper aims to introduce this translation which could not be published for reasons unknown to us.
Keywords: Salih Zeki; Asâr-ı Bâkiye; İslam Bilimi; Matematik Tarihi; Astronomi Tarihi; Türk Matematik Derneği